Peran Keluarga dalam Pendidikan Tauhid di Majlis Taklim ‘Izzatin Nisa Tangerang (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
Tawhid education is a fundamental aspect of Islamic education that serves as the foundation for the formation of faith and individual religious character. The family plays a crucial role as the primary educational environment in instilling the values of Tawhid from an early age. However, in modern social realities, the role of families in Tawhid education often faces various challenges, necessitating support from non-formal Islamic educational institutions. This study aims to describe the role of families in Tawhid education through their involvement in the Majlis Taklim ‘Izzatin Nisa Tangerang. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation of the Majlis Taklim administrators, the congregation, and ongoing learning activities. The results show that families play an active role in Tawhid education through parental role models, the habit of worship at home, and the strengthening of understanding of the faith gained from the Majlis Taklim activities. The Majlis Taklim ‘Izzatin Nisa serves as an educational tool that strengthens the congregation's understanding of Tawhid and encourages its implementation in family life. Thus, the synergy between families and religious study groups has been proven to contribute to strengthening monotheism education and building religious awareness within the community.